Hierarchical spinel NixCo1-xFe2O4 microcubes derived from Fe-based MOF for high-sensitive acetone sensor. Issue 16 (November 2018) - Wu, Shumin; Li, Xianliang; Xu, Yan; Wu, Junbiao; Wang, Zhuopeng; Han, Yide; Zhang, Xia
Abstract: Hierarchically spinel Ni x Co1- x Fe2 O4 (0.0 ≤  x  ≤ 0.5) microcubes were successfully prepared through a combined solvent evaporation strategy and morphology-inherited annealing treatment. By using the Fe-based metal-organic frameworks (MOFs), Fe4 (Fe(CN)6 )3, and inorganic Ni 2+ and Co 2+ acetate salts as co-templated precursors, hierarchical Ni-doped spinel CoFe2 O4 architecture can be obtained, and the Ni/Co substitution ratios can be controlled systematically. The obtained cubic hierarchical Ni x Co1- x Fe2 O4, (0.0 ≤  x  ≤ 0.5) composites presented highly acetone sensing properties, among which the Ni0.1 Co0.9 Fe2 O4 composite showed the strongest response performance (with gas response ( R g / R a ) of 1.67 at 240 °C) and excellent reproducibility (for at least 14 cycles), and the proposed acetone sensing mechanism was also discussed. The presented solvent evaporation and co-templated strategy may allow precisely access to fabricating other heteroatom doped inorganic materials with intriguing morphologies, architectures, chemical compositions and tunable sensing properties. Graphical abstract: Hierarchical Ni x Co1- x Fe2 O4 (0.0 ≤  x  ≤ 0.5) micro/nano-cubes prepared via inorganic salt-assisted morphology-inherited annealing treatment of Fe-MOF featured selective and reproductive sensing performance towards acetone. fx1